1997
DOI: 10.1128/iai.65.4.1486-1496.1997
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte-derived macrophages infected with virulent Shigella flexneri in vitro undergo a rapid cytolytic event similar to oncosis but not apoptosis

Abstract: Infection of human monocyte-derived macrophages in vitro with virulent Shigella flexneri resulted in cell death which involved rupture of the plasma membrane, cell swelling, disintegration of ultrastructure, and generalized karyolysis. These features bore resemblance to oncosis and are in striking contrast to previously described observations of mouse macrophages, where a similar infection by virulent Shigella resulted in cell death by apoptosis. Cell death by oncosis in human macrophages was confirmed by lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 47 publications
12
40
1
Order By: Relevance
“…The above data are consistent with previous studies [4,5] that indicate that the outcome of the interaction between Shigella and host macrophage cells depends largely on both bacterial virulence and the stage of di¡erentiation of the host cells. In the experiments described here, M90TS is able to escape from J774 phagocytic vacuoles more rapidly than from phagocytic vacuoles of U937 cells, and thus appears to exert a greater cytotoxic e¡ect to J774 cells.…”
Section: Sh4 and Sh42 Grew Slower Than M90ts In U937 Cellssupporting
confidence: 93%
See 2 more Smart Citations
“…The above data are consistent with previous studies [4,5] that indicate that the outcome of the interaction between Shigella and host macrophage cells depends largely on both bacterial virulence and the stage of di¡erentiation of the host cells. In the experiments described here, M90TS is able to escape from J774 phagocytic vacuoles more rapidly than from phagocytic vacuoles of U937 cells, and thus appears to exert a greater cytotoxic e¡ect to J774 cells.…”
Section: Sh4 and Sh42 Grew Slower Than M90ts In U937 Cellssupporting
confidence: 93%
“…Virulent Shigella can induce either apoptosis or necrosis in human-derived macrophages depending on the state of di¡erentiation of the host cells [4,5]. A recent study has further con¢rmed this observation with the use of the human monoblastic cell line U937 [15].…”
Section: Sh4 and Sh42 Grew Slower Than M90ts In U937 Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…Examples are provided by Pseudomonas aeruginosa, which can cause oncosis of macrophages by secreting type III secretion effectors (Dacheux et al, 2001). Also haemolysin-positive Escherichia coli (Fernandez-Prada et al, 1998), Brucella abortus (Pei et al, 2006) as well as Shigella flexneri (Fernandez-Prada et al, 1997) have been reported to induce cell death of macrophages morphologically consistent with oncosis. In the particular case of S. pyogenes, we have shown that oncosis of macrophages was triggered by the streptococcal cytolysins SLS and SLO.…”
Section: Discussionmentioning
confidence: 99%
“…Virulent Shigella-infected and IpaB-injected J774 cells have been reported to show morphological features typical of apoptosis [6,14]. On the other hand, Fernandez-Prada et al reported that human monocyte-derived macrophages infected with S. £exneri in vitro underwent rapid cytolytic cell death di¡erent from apoptosis [15]. Shigella-infected macrophages show rupture of the plasma membrane, cell swelling, disintegration of ultrastructure, and generalized karyolysis, which are characteristics of oncosis, a recently proposed form of cell death [16].…”
Section: Introductionmentioning
confidence: 99%